RELATIONSHIP BETWEEN THE ROLE OF FAMILIES IN DIET SUPERVISION AND THE LEVEL OF COMPLIANCE OF DIETARY MANAGEMENT AMONG TYPE 2 DIABETES MELLITUS PATIENTS IN KEBONSARI VILLAGE, CANDI SUB-DISTRICT, SIDOARJO DISTRICT - Meli Diana (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2018)
Background: The Indonesia Sehat Program is a program to improve the quality of life of the Indonesian people. The target of this program is to improve the health and nutritional status of the community through health and community empowerment efforts supported by financial protection and equitable distribution of health services. The latest estimate of the International Diabetes Federation, there are 382 million people living with Diabetes in the world in 2013. By 2035 this number is expected to increase to 592 million people.Objectives: This study aimed to determine the relationship between the role of families in diet monitoring with the level of compliance with Type II Diabetes Mellitus patients in carrying out the Diabetes Mellitus diet at Kebonsari Candi Sidoarjo.Method: This study used correlational design with a sample of 25 people. Samples were obtained using total sampling method. The instrument used to obtain data in this study is a questionnaire. The data obtained were then analyzed by using the Spearman test with p ≤ 0,01.Results: Families who play an active role in the supervision of diabetic patients with diabetes mellitus are related to the level of patient compliance in the obedient category of 44%. Based on the Spearman Rank test with p <0.01, the correlation level is 0.600. It can be concluded that there is a relationship between the role of families in diet monitoring and the level of adherence to type 2 diabetes mellitus patients in carrying out a diabetes mellitus diet has a strong level of correlation.Conclusion: Families are required to play an active role in supervising diabetics in carrying out the diabetes mellitus diet so that it can prevent complications of the disease and the quality of life of the sufferer. Key words: The Role of Families, Diet Compliance, Type 2 Diabetes Mellitus